Versatile and Tunable Poly(Ethylene Glycol)‐Based Hydrogels Crosslinked through the Ugi Reaction. Issue 12 (28th December 2020) - Padrão, Inês; Fernandes, Cláudia S. M.; Esteves, Carina; Fernandes, Tiago; Pina, Ana S.; Roque, Ana Cecília A.
Abstract: The four‐component Ugi condensation reaction has been investigated to assemble chemically crosslinked hydrogels using multivalent star‐shaped poly(ethylene glycol) components. The resulting biocompatible hydrogels are highly versatile in composition and function. It is shown that acid, aldehyde, and cyanide components can be varied yielding materials with precise structure and tunable stiffness. Additionally, the resulting hydrogels were proven extremely robust to consecutive drying‐swelling cycles. This property was explored to develop a reversible humidity colorimetric sensor gel. Overall, this work demonstrates the application of the four‐component Ugi reaction as a powerful tool to quickly generate crosslinked gels with precise control in chemical composition. Abstract : Multivalent PEG‐based hydrogels as potential sensors : The four‐component Ugi reaction allows fast and controllable crosslinking of multivalent PEG polymers. Using diverse acid, aldehyde, and cyanide components, biocompatible and versatile hydrogels with different stiffness were formed. Due to its ability to endure successive dry‐swelling cycles, these gels can be used as humidity sensors.